PENGARUH KETERSEDIAAN SUMBER BELAJAR DAN MINAT TERHADAP HASIL BELAJAR IPS KELAS VII SMPM 06 DAU - Niswatin Maghfiroh; Hayyun Lathifaty Yasri (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research is motivated by the number of teachers and social studies textbooks as learning resources which are less than the number of students, and students' interest in participating in the social studies learning process is still lacking. As a result, students achieve learning outcomes that do not meet the specified KKM. The aims of this study were to: (1) explain the effect of the availability of learning resources on social studies learning outcomes for seventh grade students of SMP Muhammadiyah 06 Dau Malang; (2) explain the effect of interest in learning on the social studies learning outcomes of students. class VII SMP Muhammadiyah 06 Dau Malang; (3) explaining the effect of the availability of learning resources and interest in learning on social studies learning outcomes for seventh grade students of SMP Muhammadiyah 06 Dau Malang. This study uses a quantitative approach with descriptive statistics. The population and samples used were all seventh-grade students of SMP Muhammadiyah 06 Dau Malang. The data analysis technique used is multiple linear regression analysis with a probability level of 0.05. The results of the study show 1) the availability of learning resources has an influence on social studies learning outcomes; 2) interest in learning has an influence on social studies learning outcomes; 3) the availability of learning resources and interest in learning affect social studies learning outcomes with a significance level of (0.01) < (0.05). Abstrak Penelitian ini dilatarbelakangi oleh jumlah guru dan buku paket IPS sebagai sumber belajar yang lebih sedikit dari jumlah siswa, dan minat siswa untuk mengikuti proses pembelajaran IPS masih kurang. Akibatnya, siswa mencapai hasil belajar yang tidak memenuhi KKM yang ditetapkan. Tujuan penelitian ini adalah untuk: (1) menjelaskan pengaruh ketersediaan sumber belajar terhadap hasil belajar IPS siswa kelas VII SMP Muhammadiyah 06 Dau Malang; (2) menjelaskan pengaruh minat belajar terhadap hasil belajar IPS siswa kelas VII SMP Muhammadiyah 06 Dau Malang; (3) menjelaskan pengaruh ketersediaan sumber belajar dan minat belajar terhadap hasil belajar IPS siswa kelas VII SMP Muhammadiyah 06 Dau Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis statistik deskriptif. Populasi dan sampel yang digunakan adalah seluruh siswa kelas VII SMP Muhammadiyah 06 Dau Malang. Teknik analisis data yang digunakan adalah analisis regresi linier berganda dengan taraf probabilitas 0.05. Hasil penelitian menunjukkan 1) ketersediaan sumber belajar memberikan pengaruh terhadap hasil belajar IPS; 2) minat belajar memberikan pengaruh terhadap hasil belajar IPS; 3) ketersediaan sumber belajar dan minat belajar berpengaruh terhadap hasil belajar IPS dengan taraf signifikansi (0.01) < (0,05).